Paul: the transition from Nazarenism to christianity - Shehu, Fatmir (SAS Publishers, India, 2018)
This study examines the role of the person of Paul in the transition of Christian religion from Nazaren-Christianity to Gentile-Christianity. The goal of this paper is to explore firstly Paul‘s turning point from being a Jew to a devout Christian and secondly his missionary activities to the Gentiles (non-Jews), which played an important role in the development of Christianity as a religion, its major teachings and thoughts. Paul‘s great concern regarding the foundation of Christian theology or what is now known as the Pauline Christian theology, is presented in this study. His real contribution is found in his teachings, where the central point is the death and resurrection of Jesus Christ of Nazareth, who after the crucifixion had risen in glory, headed a new community and guided it through his spirit. The main thrust of this paper will be on: (1) Paul‘s life and personality, (2) Paul‘s conversion from an orthodox Jew to a devout Christian, (3) Paul‘s missionary activities to the Gentiles (Non-Jews), (4) Paul‘s contribution to the foundation of Christian theology and thought (Paul‘s central doctrines of Christianity, like original sin, incarnation, crucifixion, redemption, atonement, reconciliation, resurrection, and salvation). Descriptive-analytical-philosophical methodology has been used in this study. The findings of this paper contribute significantly to the existing literature on the subject of the study of religion.